Work-piece optimization and thermal analysis for flash-less cold forging of AUV propeller hubs — FEM simulation and experiment - Othman, Abdul Rahim (2011)
In this paper three-dimensional FEM based work-piece optimization and thermal analysis for flash-less cold forging of aluminum front and back hubs of an Autonomous Underwater Vehicle (AUV) propeller is presented. The work-piece used is of AISI AL6061 and the die material is die steel (AISI D2). For front and back hubs, five cases of work-pieces of varying dimensions are simulated to obtain the optimum work-piece in terms of flash and under-filling and the optimization is verified through thermal analysis. Based on the simulation results, the flash-less cold forging is successfully done on a 100 ton C-type machine. The experimental forged samples are observed in good conformity with the simulated models